Economic and social impacts of self-help groups in india - Deininger, Klaus W. 1962- (Policy research working paper, 2009)
"Although there has been considerable recent interest in micro-credit programs, rigorous evidence on the impacts of forming self-help groups to mobilize savings and foster social empowerment at the local level is virtually non-existent, despite a large number of programs following this pattern. The authors use a large household survey to assess the economic and social impacts of the formation of self-help groups in India. They find positive impacts on empowerment and nutritional intake in program areas overall and heterogeneity of impacts between members of pre-existing and newly formed groups, as well as non-participants. Female social and economic empowerment in program areas increased irrespective of participation status, suggesting positive externalities. Nutritional benefit was more pronounced for new participants than for members of pre-existing groups. Evidence of higher consumption - but not income or asset formation - by participants suggests that at the time of the survey, the program's main economic impact had been through consumption smoothing and diversification of income sources rather than exploitation of new income sources. Evaluation of such programs in ways that allow heterogeneity of program impact can yield highly policy-relevant insights. "--World Bank web site